Value Added Tax Enforcement problem in Indonesia - RR Dewi Anggraeni; Nur Rohim Yunus; Annissa Rezki (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:Tax proceeds are state income used for public expenditures, such as fostering the sustainability of state instruments, state administration, state institutions, state assets, state development, and so on, all of which must be financed with state income. Taxes are people's contributions to the state treasury based on the mandate of Article 23 of the Republic of Indonesia's 1945 Constitution, which can be enforced without obtaining lead services (counter-achievements), can be shown directly, and are used to pay general expenses. VAT is a tax levied by the Ministry of Finance's Directorate General of Taxes. The author employs a qualitative research methodology in this paper with the goal of educating readers about VAT, particularly taxpayers doing business in Indonesia.Keywords: Value Added Tax; Tax Collection; Taxes in Indonesia Abstrak:Uang hasil pajak merupakan penghasilan negara yang dimanfaatkan untuk pengeluaran umum dalam rangka membina keberlangsungan alat-alat negara, administrasi negara, lembaga negara, aset negara, pembangunan negara, dan seterusnya yang harus dibiayai dari penghasilan negara. Pajak merupakan iuran rakyat kepada kas negara berdasarkan amanat Pasal 23 UUD NRI 1945 yang sifatnya dapat dipaksakan dengan tanpa mendapat jasa-timbal (kontra-prestasi), yang langsung dapat ditunjukkan dan yang digunakan untuk membayar pengeluaran umum. PPN merupakan pungutan di bawah kewenangan Direktorat Jenderal Pajak, Kementerian Keuangan. Dalam penulisan ini, penulis menggunakan metodologi penelitian kualitatif dengan tujuan penelitian untuk mengedukasi pembaca mengenai PPN khususnya bagi wajib pajak yang melakukan praktik usaha di Indonesia.Kata Kunci: Reformasi 98; Demokrasi; Politik Islam